ChemInform Abstract: Synthesis and Neurite Outgrowth Promoting Activity of Vibsanin B Derivatives. Issue 47 (6th November 2014) - Shao, Li‐Dong; Xu, Jun; Gao, Xiu; He, Juan; Zhao, Yu; Peng, Li‐Yan; Luo, Huai‐Rong; Xia, Chengfeng; Zhao, Qin‐Shi
Abstract A series of vibsane‐type diterpenoids with promising neurite outgrowth promoting activity is prepared from vibsanin B (I).